2018
DOI: 10.1080/17469899.2018.1555035
|View full text |Cite
|
Sign up to set email alerts
|

Application of subthreshold laser therapy in retinal diseases: a review

Abstract: Introduction: Laser photocoagulation has been a valuable tool in the ophthalmologist’s armamentarium for decades. Conventional laser photocoagulation relies on visible retinal burns as a treatment endpoint, which is thought to result in photocoagulative necrosis of retinal tissue. Recent studies have suggested that using subthreshold (ST) laser, which does not cause detectable damage to the retina may also have therapeutic effects in a variety of retinal diseases. Areas covered: We review the proposed biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…Studies performed in vitro and on animals showed a series of retinal glial cell-derived cytokines and extracellular matrix-mediated responses [ 15 ]. Experiments on rabbits and mice proved that heat shock protein (HSP) expression after subthreshold laser irradiation did not significantly differ from other more damaging energy settings [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies performed in vitro and on animals showed a series of retinal glial cell-derived cytokines and extracellular matrix-mediated responses [ 15 ]. Experiments on rabbits and mice proved that heat shock protein (HSP) expression after subthreshold laser irradiation did not significantly differ from other more damaging energy settings [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that by using the landmark pattern feature, the surgeon can choose to leave visible markers for reference and documentation of the treatment region [16]. In that study, the presence of markers or atrophic lesions after NRT therapy-was not observed with fundus autofluorescence during the follow-up (Figure 1C-1D and 2C-2D).…”
Section: -Discussionmentioning
confidence: 74%
“…Thirdly, the EpM has the Landmark Pattern feature, which enables us to treat lesions subvisible, while leaving visible markers for reference and documentation of the treatment region. And EpM can be repeated as often as necessary [16].…”
Section: -Discussionmentioning
confidence: 99%
“…2,[17][18][19]22,23,27 Implementation of the principles of modern retinal laser therapy allows effective treatment for conventional retinal laser indications, including diabetic macular edema, proliferative diabetic retinopathy, central serous chorioretinopathy, and retinal vein occlusions with improved safety allowing transfoveal treatment and early treatment, and thus improved visual results. 21,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] Moreover, modern retinal laser therapy allows effective therapeutic and preventive treatment of other important sight-threatening disorders, all neurodegenerations, precluded to conventional photocoagulation. The improved understanding of the mechanisms and neuroprotective effects of laser action introduced by SDM predicted these new laser applications.…”
Section: Introductionmentioning
confidence: 99%
“…2,[17][18][19][20][21][22] Other applications reported include pseudophakic and uveitic cystoid macular edema, retinal vasculitis, macular telangiectasia, dome-shaped maculae, macular macroaneurysms, and macular edema associated with epiretinal membranes. [33][34][35][36] Our current understanding of the therapeutic mechanism of SDM is that it acts as a physiologic "reset" stimulus, improving, and thus normalizing, RPE and hence retinal function by activating RPE heat-shock proteins (HSPs). [8][9][10][11][12][13][14][15]17,18,27,37 This effect is agnostic to the cause of retinal dysfunction, accounting for the wide range of clinical applications afforded to modern retinal laser therapy.…”
Section: Introductionmentioning
confidence: 99%